Unexpected Gating Behaviour of an Engineered Potassium Channel Kir - Fagnen, Charline; Bannwarth, Ludovic; Zuniga, Dania; Oubella, Iman; De Zorzi, Rita; Forest, Eric; Scala, Rosa; Guilbault, Samuel; Bendahhou, Saïd; Perahia, David; Vénien-Bryan, Catherine (Frontiers in Molecular Biosciences, 2021)
In this study, we investigated the dynamics and functional characteristics of the KirBac3.1 S129R, a mutated bacterial potassium channel for which the inner pore-lining helix (TM2) was engineered so that the bundle crossing is trapped in an open conformation. The structure of this channel has been previously determined at high atomic resolution. We explored the dynamical characteristics of this open state channel using an in silico method MDeNM that combines molecular dynamics simulations and normal modes. We captured the global and local motions at the mutation level and compared these data with HDX-MS experiments. MDeNM provided also an estimation of the probability of the different opening states that are in agreement with our electrophysiological experiments. In the S129R mutant, the Arg129 mutation releases the two constriction points in the channel that existed in the wild type but interestingly creates another restriction point.